1977
DOI: 10.1111/j.1469-8137.1977.tb04849.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature on Acetylene Reduction by Mats of Blue‐green Algae in Sub‐tropical Grassland

Abstract: SUMMARYTemperature is the main factor governing the rate of acetylene reduction by mats of bluegreen algae in sub-tropical kilcuyu lawns. High midday temperatures (40°C at soil surface) inhibit acetylene reduction and low temperatures prior to dawn reduce the rate of nocturnal acetylene reduction. Data obtained from laboratory studies on algal mats and on Nostoc isolated from the mats are in agreement with those from in situ measurements confirming an acetylene reduction of 30-35°C with inhibition above 40°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…That is, given sufficient hydration and access to carbon stores, temperature is the next most important factor influencing N fixation rates. Similar to the results of others (Jones, 1977e;Liengen, 1999b;Zielke et al, 2002Zielke et al, , 2005, NA in biocrusts on Loess Plateau showed a significant response to temperature. The optimal activity temperature for crusts from the Loess Plateau region was 35e40 C for the early successional stages and 30e40 C for the later successional stages.…”
Section: Nitrogenase Activity Response To Temperaturesupporting
confidence: 91%
“…That is, given sufficient hydration and access to carbon stores, temperature is the next most important factor influencing N fixation rates. Similar to the results of others (Jones, 1977e;Liengen, 1999b;Zielke et al, 2002Zielke et al, , 2005, NA in biocrusts on Loess Plateau showed a significant response to temperature. The optimal activity temperature for crusts from the Loess Plateau region was 35e40 C for the early successional stages and 30e40 C for the later successional stages.…”
Section: Nitrogenase Activity Response To Temperaturesupporting
confidence: 91%
“…T h e response of the algal mats to temperature (Fig. 2) was similar to that obtained for other sub-tropical algal mats (Jones, 1977b), and to tropical algae from Nigeria and Brazil (Stewart et a l . , 19781, and show that they are able to survive and reduce acetylene in all of the temperature met with in the field during the experimental period.…”
Section: Discussionsupporting
confidence: 59%
“…In this study the temperature could be measured using only a mercury thermometer at the soil/grass surface. In the South African study soil surface temperatures were measured using a Sekunden thermometer probe which gave readings 10 OC higher at the algal mat surface than those obtained with a mercury thermometer (Jones, 1977b). Hence, it is likely that the midday temperature of the algal mat surface on 16 January in Florida was well above 40 O C .…”
Section: Discussionmentioning
confidence: 99%
“…There are other reports showing that nitrogen fixation in tropical cyanobacteria is lower during the middle of the day (Potts, 1979;Whitton & Potts, 1982). Such reductions have been shown to be caused either by the inhibitory effects of high light intensities (Mague, Mague & Holm-Hansen, 1977) or by high temperatures (Jones, 1977c). In this study the likely cause of the mid-day drop in nitrogenase activity is a reduction in the light intensity during cloud cover.…”
Section: Effects Of Salinity Desiccation and Temperaturementioning
confidence: 67%
“…Nitrogenase activity in heterocystous cyanobacteria has also been shown to be dependent on the carbon reserves of the colonies (Jones, 1977c(Jones, , 1989. It is likely, therefore, that the increased inhibition by DCMU of Calothrix sp.…”
Section: Effects Of Dcmumentioning
confidence: 99%